2001
DOI: 10.1080/152165401317291183
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Cationic Antibacterial Agents Berberine, Palmatine, and Benzalkonium Through Bimolecular Planar Phospholipid Film and Staphylococcus aureus Membrane

Abstract: SummarySome organic cations are known to be electrophoretically imported into bacterial cells and actively extruded from these cells by multidrug resistance (MDR) pumps. We have studied penetration of plant antimicrobial agents berberine and palmatine and synthetic antiseptic benzalkonium chloride through black planar phospholipid membrane (BLM) and membrane of Staphylococcus aureus cells. Gradients of these cations across BLM generated an electric potential difference. Penetrating anion tetraphenyl borate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 13 publications
(15 reference statements)
3
37
0
Order By: Relevance
“…The present study observed that IMP significantly increased the intracellular BBR fluorescence. BER has also been reported to exert its effects via targeting the cytoplasmic membrane and intra-nuclear DNA (18,29). Collectively, based on the present results, it may be speculated that IMP had synergistic effects with BEB via increasing the accumulation of BEB in the intracellular space of P. aeruginosa cells.…”
Section: Discussionmentioning
confidence: 58%
“…The present study observed that IMP significantly increased the intracellular BBR fluorescence. BER has also been reported to exert its effects via targeting the cytoplasmic membrane and intra-nuclear DNA (18,29). Collectively, based on the present results, it may be speculated that IMP had synergistic effects with BEB via increasing the accumulation of BEB in the intracellular space of P. aeruginosa cells.…”
Section: Discussionmentioning
confidence: 58%
“…We found that Berberis plants produce 5Ј-MHC-D, which completely blocked NorA and acted in synergy with berberine (45,46). In the absence of efflux, berberine, a hydrophobic cation, accumulates in the cells of microbial pathogens, and the accumulation is driven by the membrane potential (41). Active accumulation in the pathogen is an at- tractive property for an antimicrobial, and berberine inspired the design of a cationic polymer with a "sterile" surface (47) that is not subject to MDR-dependent resistance (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cationic compounds such as ethidium are electrophoretically imported into energized bacterial cells, and this process is driven by the ⌬ (inside negative). Consequently, significant levels of accumulation of cationic compounds can occur even in the absence of an active uptake system (20,21). Binding of ethidium to the cellular polynucleotides can further contribute to drug accumulation in cells relative to the environment.…”
Section: Figmentioning
confidence: 99%